2020
DOI: 10.7717/peerj.9878
|View full text |Cite
|
Sign up to set email alerts
|

Development of limb bone laminarity in the homing pigeon (Columba livia)

Abstract: Background Birds show adaptations in limb bone shape that are associated with resisting locomotor loads. Whether comparable adaptations occur in the microstructure of avian cortical bone is less clear. One proposed microstructural adaptation is laminar bone in which the proportion of circumferentially-oriented vascular canals (i.e., laminarity) is large. Previous work on adult birds shows elevated laminarity in specific limb elements of some taxa, presumably to resist torsion-induced shear strain during locomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 68 publications
(126 reference statements)
2
14
0
2
Order By: Relevance
“…However, as of the Ornithothoraces, the thickness of these marginal bone layer decreases considerably, in general rarely exceeding 35% of the total bone cortex in the case of the ICL and 15% in the case of the OCL (Figures 3‐7; Tables 3 and 4). The pattern for the marginal bone layers is similar to what is observed in the Neornithes, in general never exceeding 15 to 20% of the total bone cortex (Bourdon et al., 2009; Chinsamy, 1995; Dabee, 2013; de Margerie, 2002; McGuire et al., 2020; Ponton et al., 2004; Starck & Chinsamy, 2002). This decrease in the thickness of the ICL becomes more prominent in the non‐ornithurine euornithians and the extinct ornithurines exhibiting uninterrupted bone growth.…”
Section: Inner Circumferential Layer Versus Outer Circumferential Layersupporting
confidence: 73%
See 2 more Smart Citations
“…However, as of the Ornithothoraces, the thickness of these marginal bone layer decreases considerably, in general rarely exceeding 35% of the total bone cortex in the case of the ICL and 15% in the case of the OCL (Figures 3‐7; Tables 3 and 4). The pattern for the marginal bone layers is similar to what is observed in the Neornithes, in general never exceeding 15 to 20% of the total bone cortex (Bourdon et al., 2009; Chinsamy, 1995; Dabee, 2013; de Margerie, 2002; McGuire et al., 2020; Ponton et al., 2004; Starck & Chinsamy, 2002). This decrease in the thickness of the ICL becomes more prominent in the non‐ornithurine euornithians and the extinct ornithurines exhibiting uninterrupted bone growth.…”
Section: Inner Circumferential Layer Versus Outer Circumferential Layersupporting
confidence: 73%
“…Our comparisons of the studied osteohistological features in basal avians indicate that the microstructure and formation observed in extant Neornithes for the ICL and OCL originated prior to the crown, specifically as of the Ornithothoraces. A potential explanation for this noticeable decrease of the thickness in these two marginal bone layers is probably the evolutionary increase in bone growth rates throughout the basal avians to reach values similar and/or equal to those observed in extant neornithines, which in general reach full somatic and sexual maturity in more or less a year (Figure 8; Brusatte et al., 2015; Chinsamy‐Turan, 2005; McGuire et al., 2020; Ponton et al., 2004; Prondvai et al., 2020; Starck & Ricklefs, 1998). In the case of the ICL, there is another reasonable explanation which is most likely associated with the increase in medullar resorption during the late ontogenetic stage prior to full somatic maturity (McGuire et al., 2020).…”
Section: Inner Circumferential Layer Versus Outer Circumferential Layermentioning
confidence: 92%
See 1 more Smart Citation
“…Certainly, a larger sample size and additional sectioning of each element would provide a more rigorous test, but preliminary results indicate that laminar vascularity does not dominate the humerus in a majority, or even many, birds. This corroborates recent findings in homing pigeons (McGuire et al, 2020) and bats (Lee & Simons, 2015). Of particular note, McGuire et al ( 2020) observed a higher degree in laminarity in younger individuals, with vascular orientation becoming increasingly longitudinal with maturity.…”
Section: Mechanical Signalsupporting
confidence: 91%
“…Galloanseriforms understandably draw the attention of researchers because of their importance in the poultry industry, and because specimens are readily available since they are domestically bred and farmed. Comparatively few studies have investigated histological characteristics outside of these early-diverging clades (de Margerie et al, 2004;Watanabe, 2018;McGuire et al, 2020).…”
Section: Introductionmentioning
confidence: 99%